Temperature Matters: Annealing Effects on Silver Protection and Tungsten Oxidation in W@Ag Core-Shell Powder - Strakosova, Angelina; Lejcek, Pavel; Vonavkova, Ilona; Dalibor, Vojtech (Manufacturing Technology Journal, 2025)
Core-shell powders have been extensively studied due to their complex structure and wide range of applications. W@Ag core-shell powders are particularly interesting due to the synergy between the tungsten and silver, which can be beneficial in the electronics industry. However, knowledge of their thermal stability is limited, particularly concerning the impact of annealing temperatures on structural integrity and oxidation resistance. In this work, W@Ag core-shell powder was heat-treated in the temperature range 100-700 °C for 1 h in air. Investigation of the microstructural changes using scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy showed that the limiting temperature is 500 °C, when the shell began to decompose and the core began to oxidize. Moreover, X-ray diffraction analysis determined that the phase composition of the thus heat-treated material consisted of approxi-mately 50 % Ag and 50 % Ag2WO4.
Keywords: Tungsten; Silver; Core-shell powder; Annealing; Oxidation